A Brief Description of Samara Ergonyms - Khokhlova, Anna Alekseevna (Acta Universitatis Lodziensis. Folia Linguistica Rossica, 2022)
The purpose of the article is to consider a specific group of ergonyms associated with the regional culture, history, development, and geolocation of the Samara region. The article is aimed at finding out the main characteristic features of the names of enterprises and organizations (ergonyms) in Samara. The author uses descriptive comparative method. To provide the material and examples of ergonym, the methods of association, links and semantic map are used. The provided description makes us think that the regional peculiarities of ergonyms are an essential part of the national-cultural component. It can be realized with the help of the realities associated with geolocation or specific features of the social, cultural, historical, ethnic development of a state and nation as a whole. It can be concluded that modern trends affect the ergonymic space of a city and its ergonymicon. The national-territorial component is capable of performing a parole function. There are certain ergonymic models associated with territorial identity, including abbreviations and acronyms, as well as contaminations of different types. The analysis and the study results of Samara ergonyms are supposed to be a valuable material for investigation of proper names of enterprises, institution, firms etc. There are further prospects for studying a number of onomastic issues. The study results can be useful in solving brand and rebrand problems.